Looking Through the COVID-19 Window of Opportunity: Future Scenarios Arising From the COVID-19 Pandemic Across Five Case Study Sites - Richter, Isabell; Avillanosa, Arlene; Cheung, Victoria; Goh, Hong Ching; Johari, Sofia; Kay, Susan; Maharja, Carya; Nguyễn, Thu Hà; Pahl, Sabine; Sugardjito, Jito; Sumeldan, Joel; van Nguyen, Quyen; et al. (Frontiers in Psychology, 2021)
The COVID_19 pandemic has caused (and continues to cause) severe disruption in global and local economies and has forced countries, societies, and individuals to adapt quickly to the unprecedented and unpredictable situation. Despite the obvious negative consequences of the pandemic, many have called for efforts to identify transformative opportunities for sustainable development throughout this disorderly time. In the present paper we explore such potential opportunities in the context of an interdisciplinary, international research project, which is focussing on sustainable marine management in biosphere reserves and marine parks in Southeast Asia. During a virtual workshop conducted as part of the GCRF Blue Communities project, future scenarios were developed depicting potential effects of the COVID_19 pandemic on five case study sites. All of these sites are in areas of internationally recognised outstanding ecological value (Taka Bonerate Kepulauan-Selayar Biosphere Reserve, Indonesia; Tun Mustapha Park, Sabah, Malaysia; Palawan Biosphere Reserve, Philippines; North Devon Biosphere Reserve, United Kingdom; Cu Lao Cham- Hoi An Biosphere Reserve, Vietnam). At the macro-level, economies, governance structures and societal norms are undergoing big changes. At the micro-level, the livelihoods, lifestyles, and backyards of local residents have to adapt. Collaboratively, we explored how COVID_19 posed challenges in our five case study sites, but we also focused on potential COVID_19-related windows of opportunity for future sustainable development. Opportunities could be identified in all three pillars of sustainable development: the environment, the society, and the economy. Although remarkable similarities can be found across all five sites, we conclude that there cannot be a ‘one size fits all’ solution to turn the tide towards achieving sustainable development. Just as before the pandemic, sustainable development starts with engaging with and understanding local environments, challenges and situations, building on local knowledge and developing tailor-made solutions for the communities in situ.